ANALYSIS OF SERVICE LEVEL OF PERINTIS INDEPENDENCE ROAD KM. 017 – Km. 018 MAKASSAR CITY - FITRIAH (Magister Teknik Sipil Pps Universitas Muslim Indonesia, 2021)
Road Independence Perintis City of Makassar is an urban road, from direct observation in the field on Jalan Perintis Kemerdekaan Km. 017 – Km. 018 Makassar City occurs several times of congestion causing long queues, namely during peak hours in the afternoon, at sunset until at night under certain conditions. Some of the traffic jams are temporary and some are routine, this is caused by the number of certain road conditions that are damaged, the presence of vehicles entering and leaving the road, the number of road users who have not obeyed the rules in an orderly manner, thus disrupting the smooth flow of traffic which can cause congestion. traffic. This study aims to (1) analyze the traffic conditions and characteristics on the Perintis Kemerdekaan Km. 017 – Km. 018 Makassar City, and (2) Analyzing the value of the degree of saturation (DS) and service level indicator (LoS) for the Pioneer Independence Km. 017 – Km. 018 Makassar City.This research is a non-experimental research, descriptive exploratory, case study type with survey methods and direct observation in the field to determine the performance of the road network. The results showed that (1) light vehicles (LV), heavy vehicles (HV), motorcycles (MC) and non-motorized vehicles (UM). The peak current on the Jalan Perintis Kemerdekaan Km.017 - Km.018 west is 4728 smp/hour at 17.00 - 18.00. The speed at that hour was 0.14 km/hour with a density level of 34937 smp/km while the peak current on the East Perintis Kemerdekaan Road was 4974 smp/hour at 17.00 - 18.00. The speed at that hour was 0.14 km/hour with a density level of 36288 pcu/km. the value of road capacity (C) is 5296 pcu/hour. And (2) the value of the service level (LoS) obtained a service level of 0.89 entered into category E while in the east direction the value of the degree of saturation was 0.94. The two values ​​of the degree of saturation are in the range between 0.85 to 1.00 with lower flow conditions than service level D with traffic volume approaching road capacity and very low speed; high traffic density due to high traffic internal drag; drivers begin to experience short duration traffic jams